Regional climate of the Subtropical Central Andes using high-resolution CMIP5 models. Part II: future projections for the twenty-first century - Zazulie, Natalia (2018)
In Part I of our study (Zazulie et al. Clim Dyn, 2017, hereafter Z17) we analyzed the ability of a subset of fifteen high-resolution global climate models (GCMs) from the Coupled Model Intercomparison Project phase 5 to reproduce the past climate of the Subtropical Central Andes (SCA) of Argentina and Chile. A subset of only five GCMs was shown to reproduce well the past climate (1980–2005), for austral summer and winter. In this study we analyze future climate projections for the twenty-first century over this complex orography region using those five GCMs. We evaluate the projections under two of the representative concentration pathways considered as future scenarios: RCP4.5 and RCP8.5. Future projections indicate warming during the twenty-first century over the SCA region, especially pronounced over the mountains. Projections of warming at high elevations in the SCA depend on altitude, and are larger than the projected global mean warming. This phenomenon is expected to strengthen by the end of the century under the high-emission scenario. Increases in winter temperatures of up to 2.5 °C, relative to 1980–2005, are projected by 2040–2065, while a 5 °C warming is expected at the highest elevations by 2075–2100. Such a large monthly-mean warming during winter would most likely result in snowpack melting by late winter-early spring, with serious implication for water availability during summer, when precipitation is a minimum over the mountains. We also explore changes in the albedo, as a contributing factor affecting the net flux of energy at the surface and found a reduction in albedo of 20–60% at high elevations, related to the elevation dependent warming. Furthermore, a decrease in winter precipitation is projected in central Chile by the end of the century, independent of the scenario considered.